Olmsted syndrome: Rare occurrence in four siblings - Atishay Bukharia; Sweta Komal; V Madhu Sudhanan; Shyam Sundar Chaudhary (Wolters Kluwer Medknow Publications, 2016)
Olmsted syndrome is a very rare and severe cicatrizing keratoderma associated with periorificial lesion. Most cases are sporadic but familial occurrence has been also seen. Till now around 73 cases have been reported and none of the reported cases have 4 siblings affected from this disease. We are reporting cases of 4 siblings of age 30 year female, 26 year female, 20 year male and 10 year male who were born to a third degree consangueinous marriage and presented with palmoplantar keratoderma, periorificial hyperkeratosis, flexion deformity, pseudoainhum and contracture of digits. There was no cardiac involvement. Hence, the diagnosis of Olmsted syndrome was made and all four patients were non responsive to treatment which included topical corticosteroid, topical salicylic acid, systemic isotretinoin, systemic acitretin and oral zinc in child.